Balloon Dilatation of a Case of Tuberculous Tracheobronchial Stenoses during the Course of Antituberculous Treatment. (19th March 2015) - Nour Moursi Ahmed, Shimaa; Korrungruang, Potjanee; Saka, Hideo; Asai, Gyo; Ise, Yuko; Kitagawa, Chiyoe; Oki, Masahide
Abstract : We report a case of posttuberculosis (TB) tracheobronchial stenoses presented with progressive exertional dyspnea during the course of anti-TB treatment. An 83-year-old Japanese man was admitted for progressive dyspnea; chest X-ray and CT showed stenosis of distal trachea and left main bronchus. Pulmonary function test revealed reduction of FEV1. Balloon dilatation without stent insertion was the choice for this patient for multiple reasons with marked improvement of symptoms.